The effectiveness of BCG and interferon against non‐muscle invasive bladder cancer: a New Zealand perspective. (2nd September 2015) - O'Regan, Toni; Tatton, Michael; Lyon, Maryanne; Masters, Jonathan
Abstract : Objective: To ascertain whether the current practice at Auckland City Hospital of adding interferon to BCG in patients with high risk or recurrent non‐muscle invasive bladder cancer (NMIBC) unable or unwilling to undergo radical cystectomy is effective. Subjects and Method: This study examined all institutional cases where BCG alone had not been effective or tolerated as primary treatment for NMIBC and the next guideline agreed step of radical cystectomy was unable to be performed. We identified all patients unwilling or unable to undergo radical cystectomy due to patient co‐morbidities or preference for whom ongoing treatment and care was required and included 45 in the data analysis. Current practice at Auckland City Hospital is adding interferon α‐2b to BCG for this population group and all patients that were given this therapy with at least three years of follow up data from diagnosis were included into the study. Patients were either on maintenance BCG or single dosing. Several secondary outcomes were also assessed concurrently to the primary objective. Results: This observational study showed that adding interferon to BCG proved to be an effective therapy for both treatment and salvage therapy in this patient group with 56% of the patients disease (and recurrence) free at the time of audit. 8/45 patients died whilst undergoing treatment with two of these as a direct result of bladder cancer due to disease progression. Conclusion: This therapy has improved outcomes at our institution and has a place as a treatment of choice in this difficult to manage patient group.